2019
DOI: 10.1089/trgh.2019.0050
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Antiretroviral Therapy Among Transgender and Gender Nonconforming People Living with HIV: Findings from the 2015 U.S. Trans Survey

Abstract: Purpose: This article includes an analysis of medication adherence among transgender and gender nonconforming (TGNC) people living with HIV (PLWH) from the 2015 U.S. Trans Survey (USTS), the largest survey of TGNC people in the United States. Methods: Using data from the USTS, our analytic sample included 162 TGNC PLWH who had been prescribed antiretroviral (ART). We grouped respondents by adherent/nonadherent and compared demographic characteristics and potential adherence risk factors.Results: Approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Issues of concern identified in one study include those associated with poor mental health, substance use, violence, lack of family support, homelessness, and unemployment, all of which can compromise the ability to achieve a suppressed viral load. 47 …”
Section: Resultsmentioning
confidence: 99%
“…Issues of concern identified in one study include those associated with poor mental health, substance use, violence, lack of family support, homelessness, and unemployment, all of which can compromise the ability to achieve a suppressed viral load. 47 …”
Section: Resultsmentioning
confidence: 99%
“…In studies using convenience samples and multi-center cohorts, TGD people have been less likely to be adherent to ART than cisgender people [13][14][15]43]. TGD people with HIV have been shown to face barriers to ART adherence, with studies finding that low levels of social support [13], housing instability, and sex work are associated with lower adherence for some TGD populations [44].…”
Section: Identifying Tgd Individuals and Stratifying By Gendermentioning
confidence: 99%
“…In fact, initiation or continuation of hormone therapy in concert with ART may improve engagement and retention in HIV care along with ART adherence and achievement of viral suppression 19–21 . In an analysis of survey responses from the 2015 U.S. Transgender Survey (USTS) evaluating medication adherence among transgender and gender‐nonconforming PLWH reported that 65.8% of respondents took ART as prescribed (61% transfeminine individuals and 85.7% transmasculine individuals) 22 . Individuals reporting nonadherence to ART reported higher rates of verbal harassment, sex work, homelessness in the last year, and lower rates of engagement in medical care for HIV 22 .…”
Section: Barriers To Carementioning
confidence: 99%
“…In an analysis of survey responses from the 2015 U.S. Transgender Survey (USTS) evaluating medication adherence among transgender and gender‐nonconforming PLWH reported that 65.8% of respondents took ART as prescribed (61% transfeminine individuals and 85.7% transmasculine individuals) 22 . Individuals reporting nonadherence to ART reported higher rates of verbal harassment, sex work, homelessness in the last year, and lower rates of engagement in medical care for HIV 22 . Targeted interventions to improve ART medication adherence in this population should occur in individuals under the age of 40 years, of Black ethnicity, with unstable sociostructural conditions (i.e.…”
Section: Barriers To Carementioning
confidence: 99%